The correspondence between Hugh MacDiarmid and Sorley MacLean : an annotated edition - MacDiarmid, Hugh, 1892-1978 (Edinburgh University Press, 2010)
This is both the first complete annotated edition of the letters exchanged by these major twentieth-century Scottish poets and the first major exploration of their long friendship and literary association. Spanning nearly fifty years, from 27 July 1934 to 23 July 1978, this engaging correspondence offers a revealing and sometimes intimate look at their lively dialogical exchanges on a broad range of topics from major historical events such as the Spanish Civil War and WW II, to the mundane challenges of daily life. The introductory chapters chart the development of MacDiarmid and MacLean's end.